2021
DOI: 10.3389/fonc.2021.692535
|View full text |Cite
|
Sign up to set email alerts
|

A Metastasis-Related lncRNA Signature Correlates With the Prognosis in Clear Cell Renal Cell Carcinoma

Abstract: To explore the role of metastasis-related long noncoding RNA (lncRNA) signature for predicting the prognosis of clear cell renal cell carcinoma (ccRCC) patients. Firstly, metastasis-associated genes were identified to establish a metastasis-related lncRNA signature by statistical analysis. Secondly, the ccRCC patients were grouped into high-risk or low-risk group according to the established signature, and the different pathways between the 2 groups were identified by gene set enrichment analysis (GSEA). Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…It leads to high mortality owing to its aggressive and metastatic nature 20,21 . Recent studies have constructed signatures with m6, metastasis, glycolysis and immune-related lncRNAs to predict the prognosis of patients with ccRCC [22][23][24][25] . However, OS-related lncRNA signatures have not been constructed.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to high mortality owing to its aggressive and metastatic nature 20,21 . Recent studies have constructed signatures with m6, metastasis, glycolysis and immune-related lncRNAs to predict the prognosis of patients with ccRCC [22][23][24][25] . However, OS-related lncRNA signatures have not been constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zeng et al constructed a 6-lncRNA-based risk score which could be used for ccRCC prognosis based on RNA-sequencing data ( 26 ). Dou et al also constructed 7-metastasis-related genes that correlated with the prognosis with the metastasis-related lncRNA signature in ccRCC ( 27 ). Su et al also showed that 3-key combined lncRNA signature was successfully used to predict poor prognosis in patients with ccRCC ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that LUAD lncRNA plays an important role in prognosis and immunotherapeutic response. Several studies have developed lncRNA prognosis signatures, such as m6A-related ( Wang et al, 2021b ), ferroptosis-related ( Fei et al, 2021 ), pyroptosis-related ( Song et al, 2021 ), immune-related ( Qi et al, 2021 ), and metastasis-related lncRNA signatures ( Dou et al, 2021 ). However, NRLs are still being investigated, and their prognostic role in LUAD remains unclear.…”
Section: Discussionmentioning
confidence: 99%